Research on the Influence of Anxiety Psychology on Unsafe Behavior Among Construction Workers - Aiguo Xiong; Rongwei Hu; Na Xu; Durong Huang; Hong Fan; Yu Zhang (Applied Sciences)
Unsafe behaviors among construction workers constitute a primary cause of safety accidents, with unsafe psychological states often triggering such behaviors. Focusing on collective anxiety issues, this study introduces the standardized anxiety scale (SAS) into the construction domain to investigate the influence mechanism of anxiety psychology on construction workers’ unsafe behaviors. A hypothesized model was established, incorporating organizational climate, safety competency, and job satisfaction as mediating variables, and demographic characteristics (gender, age, educational background, work experience, anxiety level) as moderating variables. Data collected from field surveys were analyzed using SPSS 22.0 and AMOS 24.0 for correlation analysis, variance analysis, and regression analysis, while structural equation modeling (SEM) was employed to validate the theoretical model and hypotheses. The results indicate that (1) anxiety psychology exhibits a significant positive correlation with unsafe behaviors; (2) organizational climate, safety competency, and job satisfaction mediate the transmission pathways between anxiety psychology and unsafe behaviors; (3) enhancing organizational climate, improving safety competency, and ensuring job satisfaction effectively reduce safety incident rates. Additionally, this study proposes preventive measures targeting anxiety psychology across three dimensions: external environmental controls, internal self-regulation, and direct anxiety intervention. These measures provide novel perspectives for effectively reducing the occurrence of unsafe behaviors among construction workers and advancing safety governance frameworks in the construction industry.